25.6k views
2 votes
Y = 11-x
y = 2x² - 4x + 6

User Kalithlev
by
4.7k points

1 Answer

4 votes

Answer:

  • (- 1, 12), (2.5, 8.5)

---------------------------

Given system

  • y = 11 - x
  • y = 2x² - 4x + 6

Solve by elimination

  • 2x² - 4x + 6 = 11 - x
  • 2x² - 4x + 6 - 11 + x = 0
  • 2x² - 3x - 5 = 0
  • 2x² - 2 - 3x - 3 = 0
  • 2(x² - 1) - 3(x + 1) = 0
  • 2(x - 1)(x + 1) - 3(x + 1) = 0
  • (x + 1)(2x - 2 - 3) = 0
  • (x + 1)(2x - 5)=0
  • x = - 1 and x = 2.5

Find y

  • y = 11 - (-1) = 12
  • y = 11 - 2.5 = 8.5
User Andy Stannard
by
5.6k points